2019
DOI: 10.1152/ajpheart.00348.2018
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular function in patients with chronic obstructive pulmonary disease: the impact of exercise training

Abstract: This study examined cerebral blood flow (CBF) and its regulation before and after a short-term periodized aerobic exercise training intervention in patients with chronic obstructive pulmonary disease (COPD). Twenty-eight patients with COPD (forced expiratory volume in 1 s/forced vital capacity < 0.7 and <lower limit of normal) and 24 healthy control subjects participated in the study. Extracranial CBF (duplex ultrasound), middle cerebral artery velocity (MCAv; transcranial Doppler), cerebrovascular react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 59 publications
0
35
0
Order By: Relevance
“…One possible explanation might be that despite an ~18% increase in CRF, the sedentary older participants (>64 years) studied by Lewis et al (2019) had significantly lower CRF levels at baseline than our young endurance-trained men (26 to 28 years). These results support that elevated CRF is associated with diminished dCA, whereas dCA is maintained in individuals with lower CRF (20). Further research is required to elucidate whether a threshold exists above which CRF will be associated with an attenuated dCA.…”
Section: Effect Of Hiit On Dynamic Cerebral Autoregulationmentioning
confidence: 77%
See 3 more Smart Citations
“…One possible explanation might be that despite an ~18% increase in CRF, the sedentary older participants (>64 years) studied by Lewis et al (2019) had significantly lower CRF levels at baseline than our young endurance-trained men (26 to 28 years). These results support that elevated CRF is associated with diminished dCA, whereas dCA is maintained in individuals with lower CRF (20). Further research is required to elucidate whether a threshold exists above which CRF will be associated with an attenuated dCA.…”
Section: Effect Of Hiit On Dynamic Cerebral Autoregulationmentioning
confidence: 77%
“…In that report, we showed that elevated CRF was associated with increased TFA gain during 0. To our knowledge, only one other longitudinal study assessed dCA following aerobic exercise training of varied nature and intensity (20). These authors reported no training effect on dCA in healthy older sedentary participants.…”
Section: Effect Of Hiit On Dynamic Cerebral Autoregulationmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to improve the coherence values, the SNR must be increased by inducing larger BP oscillations (Van Beek et al, 2008). Squat-stand maneuvers (SSM) provide an effective, reproducible, and tolerable way of manipulating BP for the assessment of CA that can be used in healthy adult populations (Barnes, Ball, Haunton, Robinson, & Panerai, 2017Labrecque et al, 2017;Lewis et al, 2019;Smirl et al, 2014;Smirl, Hoffman, Tzeng, Hansen, & Ainslie, 2015;Zhang et al, 2009). The main drawback of SSM is the difficulty of their use in incapacitated subjects, people with mobility issues or those with cognitive impairment (Van Beek et al, 2008;Smirl et al, 2015).…”
mentioning
confidence: 99%